The Tiger's Wife - Promoting Intercultural Understanding - Olja Milosevic (CLELEjournal, 2017)
This paper presents a small case study that recorded developing intercultural understanding amongst advanced EFL students in a high school in Serbia as a result of studying The Tiger's Wife by Tea Obreht. The novel deals with the recent Balkan war and captures the mindset of people who live in the Balkans. The novel was studied over three months with a group of eight 17- to 18-year-old students of different nationalities. It provided a starting point for students in the class to come together and re-examine their views and feelings. Because the group was small, the main instructional format was classroom discussion with open-ended prompts. Host country students had stronger views on the war in their region and reacted with more intense emotion compared to their foreign peers. The host country students benefited from sharing their views, and the foreign students were motivated to explore the story through the eyes of their peers. Thus, this work of literature allowed for social constructivist negotiation. This reinforces the premise that learning takes place because of interaction in a group and highlights the potential for literature to act as a bridge for intercultural understanding.